CARDIAC AUTONOMIC NEUROPATHY RISK ESTIMATED BY SUDOMOTOR FUNCTION IN YOUNG ADULTS WITH INTELLECTUAL DISABILITY. (April 2021) - Zwack, Clara; Mcdonald, Rachael; Eikelis, Nina; Lambert, Gavin; Lambert, Elisabeth
Abstract : Objective: Young adults with Intellectual Disability (ID) are at higher risk of premature death, and present with increased prevalence of cardiovascular disease (CVD) than the general population. Cardiac autonomic neuropathy (CAN) is often associated with CVD risk factors including diabetes mellitus, metabolic syndrome and hypertension. Hence, it may be a predictor for cardiovascular morbidity and mortality. Screening for CAN risk through assessment of sudomotor function has been introduced as a method for early detection of autonomic dysfunction. Design and method: Adults with ID aged 18–45 years (n = 31) were compared to the general population (GP) (n = 29). Seated blood pressure, arterial stiffness (Pulse Wave Velocity [m/s] measured with Sphygmacor) and sudomotor function (measured with SUDOSCAN) were assessed. Results: Hand and feet electrical skin conductance (ESC) were lower in adults with ID ([Feet] ID = 72.8 microsiemens, GP = 80.4 microsiemens; p = 0.021 [Hands] ID = 65.6 microsiemens, GP = 76.8 microsiemens; p = 0.013) indicating elevated risk for CAN in the ID cohort. ESC in the ID population did not correlate with arterial stiffness, blood pressure nor body mass index (BMI), with both groups showing similar mean systolic blood pressures (ID = 127mmHg, GP = 122mmHg; p = 0.10) and PWV (ID = 8.0m/s, GP = 7.8m/s; p = 0.81), despite elevated BMI in the ID cohort (ID = 31.4 kg/m2, GP = 25.9 kg/m2; p = 0.002). However, ESC was related to Hb1Ac concentration, which was elevated in those with ID (ID = 34.4mmol/mol, GP = 29.7mmol/mol; p = 0.002). Conclusions: Our data indicates that sudomotor dysfunction is present in adults with ID and this was associated with impaired glucose metabolism. This suggest that CAN may play a role in the early development of CVD in young adults with ID. Given the increasing urgency to provide young individuals living with ID with the means to improve their health and wellbeing, screening for CAN could prove a useful tool in early detection of CVD risk, before the development of other typical risk factors including arterial stiffness and hypertension.